External Quality Assessment of a DNA Sequence-Based Scheme for Epidemiological Typing of Legionella pneumophila by an International Network of Laboratories - Afshar, Baharak (American Society for Microbiology, 2007)
We report the results of an international external quality assessment (EQA) program to assess the performance of laboratories in genotyping Legionella pneumophila isolates using the standard European Working Group for Legionella Infections sequence-based typing protocol. Three coded distributions of L. pneumophila isolates were sent to laboratories in 12, 14, and 20 countries, respectively. The data were returned by 11 of 16, 18 of 19, and 27 of 29 centers, respectively. Incomplete submission of data resulted in exclusion from certain aspects of the analyses. The number of centers achieving 100% score, for all loci tested, rose successively from 50% (5 of 10) for the first EQA distribution, to 56% (9 of 16) for the second EQA distribution, to 76% (19 of 25) for the third EQA distribution. A number of additional centers made only a few errors (one to three) in each distribution. Sequence data from the first two distributions were collected in flat text file format and using specially developed software, the sequence quality tool (SQT), in the third distribution. The SQT allows users to upload trace files in standard file formats, automates basecalling using phred and phrap software, contig assembly, trimming, and matching against a reference library. The program described here allow users an independent measure of sequence quality, and such schemes are vital in order to identify strengths and weakness in centers responsible for the generation of genotyping data in legionella outbreak investigation. The present study demonstrates that DNA sequence data can be highly reproducible but, when independently assessed, in practice frequently falls short of this goal. However, experience and training in the methodology results in increased performance.